2021
DOI: 10.1007/s00592-021-01754-2
|View full text |Cite|
|
Sign up to set email alerts
|

Glucose control in diabetes during home confinement for the first pandemic wave of COVID-19: a meta-analysis of observational studies

Abstract: Aim To assess the effect on glycaemic control of confinement due to lockdown measures, during COVID-19 pandemic, in people with type 1 (T1DM) and type 2 (T2DM) diabetes. Methods Meta-analysis of observational studies reporting measures of glucose control and variability before and during and/or after periods of confinement caused by COVID-19 in 2020 and/or 2021. Results We included 27 studies on T1DM. No significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 60 publications
8
38
3
Order By: Relevance
“…The findings of this review in respect of the blood glucose parameters would appear to confirm the result of a previous systematic review [31] which reported that the COVID-19 lockdown resulted in short-term worsening of glycaemic control in patients with type 2 diabetes. However, the result is different from the outcome of a previous meta-analysis of observational studies [17] which showed that COVID-19 lockdown had no detrimental effect on glycated haemoglobin in either patients with type 1 diabetes or type 2 diabetes, and that it led to a reduction in mean glucose and glucose variability in patients with type 1 diabetes. Variations in the designs of the studies and differences in the countries where the studies were conducted may explain the differences in the findings of our review compared with the previous review by Silverii et al [17].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The findings of this review in respect of the blood glucose parameters would appear to confirm the result of a previous systematic review [31] which reported that the COVID-19 lockdown resulted in short-term worsening of glycaemic control in patients with type 2 diabetes. However, the result is different from the outcome of a previous meta-analysis of observational studies [17] which showed that COVID-19 lockdown had no detrimental effect on glycated haemoglobin in either patients with type 1 diabetes or type 2 diabetes, and that it led to a reduction in mean glucose and glucose variability in patients with type 1 diabetes. Variations in the designs of the studies and differences in the countries where the studies were conducted may explain the differences in the findings of our review compared with the previous review by Silverii et al [17].…”
Section: Discussioncontrasting
confidence: 99%
“…However, the result is different from the outcome of a previous meta-analysis of observational studies [17] which showed that COVID-19 lockdown had no detrimental effect on glycated haemoglobin in either patients with type 1 diabetes or type 2 diabetes, and that it led to a reduction in mean glucose and glucose variability in patients with type 1 diabetes. Variations in the designs of the studies and differences in the countries where the studies were conducted may explain the differences in the findings of our review compared with the previous review by Silverii et al [17]. Furthermore, the inclusion of studies involving people with type 1 and type 2 diabetes was a primary difference our review and the earlier reviews [17,31].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As such, our results support and expand those recently published by Silverii et al [31] as other features such as estimated HbA1c and use of the sensor have been included.…”
Section: Discussionsupporting
confidence: 92%
“…Observational studies have also investigated the impact of lockdown on pre-existing cardiometabolic diseases. A meta-analysis including 10,765 patients with diabetes (1174 with type 1 and 9591 with type 2) reported an improvement in glycemic control during lockdown in type 1 diabetes, and no significant effect on glucose control in type 2 diabetes [54]. Although the information on the share of patients working from home was not available in several of the studies included in this meta-analysis, the increased time available to cope with complex diabetes management, such as glucose monitoring and insulin titration, may at least partially explain the better glycemic control during the lockdown reported in type 1 diabetes patients who stayed home.…”
Section: Working From Home and Cardiometabolic Diseasementioning
confidence: 99%